Meaningful form : parallelism and inverse parallelism in catullus, tibullus and horace. - Van der Riet, Jacobus Werndly (My University, 1998)
All the poems of Catullus and Tibullus and the first three books of Horace's Odes are investigated tor structures of parallelism and inverse paralelism (chiasmus) and thus the extent to which these devices were used is determined. Such structures are demonstrated for the first time for several poems. Sometimes additions or modifications are made to the structural analyses of other scholars, and sometimes their findings are confirmed. The notion that inverse parallelism was seldom used by Roman authors is dispelled. The freedom with which these devices were used, resulting in a great variety of deviations from strictly symmetrical structures, is demonstrated Both common and idiosyncratic features in the use of the devices by the three authors are shown. Several poems of each author are discussed to illustrate that the demonstration of a structure of parallelism or inverse parallelism is in itself an interpretative act, which can at the same time serve as a basis for further interpretation. In particular it is shown that structures of inverse parallelism often, if not always, iconically reflect the meaning of the poem (hence the title of the thesis) This ability or structures of inverse parallelism to reflect the meaning of the poem may partly account for the fact that they are used more frequently than are structures of parallelism. In the poems discussed structures of inverse parallelism iconically reflect the ideas of reversal, cyclical movement, non-progression/deadlock, balance and/or contrast and enclosure, as well as combinations of the above, such as a spiral (both progression and non-progression) or the combination of reversal and nonprogression. Continuity between the structural methods of Greek and Roman authors is demonstrated, and a theoretical framework is provided, which answers the questions how such structures can be determined, and what purposes, both practical and poetic, they serve. A literary-critical awareness of inverse parallelism in Antiquity is demonstrated. St. Augustine, especially, has a fairly developed theoretical frame of reference on the subject, in his De Genest ad Litteram
A thesis submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy.
Keywords: Catullus, Gaius Valerius -- Criticism and interpretation.; Horace -- Criticism and interpretation.; Latin poetry -- History and criticism.; Greek poetry -- History and criticism.; Parallelism (Linguistics)